The influence of responsible leadership on teachers’ green behavior: The mediating role of psychological capital - Wang, Xinyi; Kou, Fengtian; Zhu, Kexuan (Frontiers in Psychology, 2023)
This research aimed to explore the impact of responsible leadership on teachers’ green behavior in Chinese university, and applied psychological capital as a mediator variable to establish a research model. A questionnaire was conducted with 303 teachers using convenience sampling. SPSS version 19 was used to analyze the data and Sobel was used to test the mediating relationships. The results show that responsible leadership has a positive yet significant effect on teachers’ green behavior. It also shows positive impact on psychological capital. Furthermore, psychological capital is shown to positively impact teachers’ green behavior, while having a mediating effect between responsible leadership and teachers’ green behavior. This study enriches the research of teachers’ green behavior and fill the gap in previous education management research. The research conclusions enable managers to better understand teachers’ green behavior and provides them with theoretical guidance for promoting psychological capital and improving teachers’ green behavior.